g-PAT revitalising productivity growth in green construction projects (GCP) / Noor Aisyah Asyikin Mahat, Prof. Sr. Dr. Hamimah Adnan and Sr. Dr. Norazian Mohammad Yusuwan - Mahat, Noor Aisyah Asyikin; Adnan, Hamimah; Norazian, Mohammad Yusuwan (College of Built Environment, 2023)
Productivity is often used as a performance indicator in construction projects, also to evaluate the effectiveness of building project performance.